BRAF V600E, TERT promoter mutations and CDKN2A/B homozygous deletions are frequent in epithelioid glioblastomas: a histological and molecular analysis focusing on intratumoral heterogeneity. (5th December 2017) - Nakajima, Nozomi; Nobusawa, Sumihito; Nakata, Satoshi; Nakada, Mitsutoshi; Yamazaki, Tatsuya; Matsumura, Nozomi; Harada, Kenichi; Matsuda, Hadzki; Funata, Nobuaki; Nagai, Shoichi; Nakamura, Hideo; Sasaki, Atsushi; et al.
Abstract: Epithelioid glioblastoma (E‐GBM) is a rare aggressive variant of IDH‐wildtype glioblastoma newly recognized in the 2016 World Health Organization classification, composed predominantly of monotonous, patternless sheets of round cells with laterally positioned nuclei and plump eosinophilic cytoplasm. Approximately 50% of E‐GBM harbor BRAF V600E, which is much less frequently found in other types of glioblastomas. Most E‐GBM are recognized as primary/ de novo lesions; however, several E‐GBM with co‐ or pre‐existing lower‐grade lesions have been reported. To better understand associations between E‐GBM and the lower‐grade lesions, we undertook a histological and molecular analysis of 14 E‐GBM, 10 of which exhibited lower‐grade glioma‐like components (8 E‐GBM with co‐existing diffuse glioma‐like components, 1 E‐GBM with a co‐existing PXA‐like component and 1 E‐GBM with a pre‐existing PXA). Molecular results demonstrated that the prevalence of BRAF V600E, TERT promoter mutations and CDKN2A/B homozygous deletions in E‐GBM were 13/14 (93%), 10/14 (71%) and 11/14 (79%), respectively, and concurrent BRAF V600E, TERT promoter mutations and CDKN2A/B homozygous deletions were observed in 7/14 (50%) of E‐GBM. These alterations were also frequently seen in the lower‐grade lesions irrespective of the histology. Genetic analysis including array comparative genomic hybridization performed for 5 E‐GBM with co‐ and pre‐existing lower‐grade components revealed that all molecular changes found in the lower‐grade components were also observed in the E‐GBM components, and additional changes were detected in the E‐GBM components. In conclusion, E‐GBM frequently exhibit BRAF V600E, TERT promoter mutations and CDKN2A/B homozygous deletions and these alterations tend to coexist in E‐GBM. Taken together with the facts that only one PXA preceded E‐GBM among these lower‐grade lesions, and that co‐occurrence of BRAF V600E, TERT promoter mutations and CDKN2A/B homozygous deletions have been reported to be rare in conventional lower‐grade diffuse gliomas, the diffuse glioma‐like components may be distinct infiltrative components of E‐GBM, reflecting intratumoral heterogeneity.